A Māori reflection on Spinoza’s primordial - Mika, Carl (Interstices: Journal of Architecture and Related Arts, 2021)
Māori philosophy is at an exciting point as it looks to other sources for inspiration. In this paper, I refer to some key Māori concepts and terms with Spinoza’s notion of primordial substance in mind. Some Māori terms such as ira (the manifestation and persistence of a thing), whakaaro (indebtedness to a primordial substance) and Papatūānuku (primordial substance) are relevant here. I do not seek to compare Spinoza and Māori thought as such but instead to work with Māori concepts and terms with Spinoza in the background.